Interactive Virtual Reality For Fun Mathematics Learning With Deep Understanding At SMP Swasta Ar-Rahman Percut - Herman Mawengkang; Syahril Efendi; Muliawan Firdaus (Institute of Computer Science (IOCS), 2021)
This partnership program was intended to solve problems that arose at SMP Swasta Ar-Rahman Percut such as the lack of teacher skills in developing learning media to foster students’ motivation and implementing online teaching that optimizes the use of technology. In the context of online learning, such difficulties will increase. The solutions offered were training through workshops on the development of interactive virtual reality (VR) using OpenSpace3D and assistance in the implementation. Five stages: Learn, Teach, Evaluate, Acknowledge, and Fostering in the method were held sequentially. Adult learning principles, focusing on experiential learning and self-motivation, were applied to encourage participants and instructors to actively participate. Results showed that the program has made a significant impact on teachers' skills in developing and implementing interactive VR in fun mathematics online learning.